2015
DOI: 10.1371/journal.pone.0139622
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of EEG Source Analysis Based Repetitive Transcranial Magnetic Stimulation for the Treatment of Tinnitus

Abstract: ObjectiveRepetitive Transcranial Magnetic Stimulation (rTMS) is a novel therapeutic tool to induce a suppression of tinnitus. However, the optimal target sites are unknown. We aimed to determine whether low-frequency rTMS induced lasting suppression of tinnitus by decreasing neural activity in the cortex, navigated by high-density electroencephalogram (EEG) source analysis, and the utility of EEG for targeting treatment.MethodsIn this controlled three-armed trial, seven normal hearing patients with tonal tinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Moreover, rTMS treatment had a significant effect in patients without sleep disturbance. Nonauditory areas, such as the frontoparietal areas and limbic areas, have been suggested to be involved in the pathophysiology of tinnitus, as evidenced by the functional imaging data in our previous study [6]. These interactions between auditory and nonauditory brain regions may explain why tinnitus is perceived as bothersome.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Moreover, rTMS treatment had a significant effect in patients without sleep disturbance. Nonauditory areas, such as the frontoparietal areas and limbic areas, have been suggested to be involved in the pathophysiology of tinnitus, as evidenced by the functional imaging data in our previous study [6]. These interactions between auditory and nonauditory brain regions may explain why tinnitus is perceived as bothersome.…”
Section: Discussionmentioning
confidence: 72%
“…As described in our previous study [6], rTMS consisted of 1000 stimuli at 1 Hz daily and 110% of the motor cortex threshold for 5 consecutive days per week (Monday to Friday) for 2 weeks. For repetitive pulses, TMS was delivered through a focal figure-eight magnetic coil connected to a magnetic stimulator (MagPro R30; MagVenture, Farum, Denmark).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested a strong positive association between the subjective strength of tinnitus and the magnitude of the shift in the tinnitus frequency in the auditory cortex [ 15 ]. Other studies indicated that tinnitus results from changes in the firing patterns of neurons in the central auditory system and from changes in burst firing and neural synchrony [ 16 ]. These results suggest a potential correlation between spontaneous neural activity and tinnitus, as well as a causal link between the characteristic frequency that dominates the reorganized neural map and the tinnitus pitch [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-density electroencephalography (HD-EEG), which yields data with a high temporal resolution and reasonable spatial resolution, has been identified recently as a powerful tool for studies of dynamic brain activity [ 16 , 18 , 19 ]. EEG enables the noninvasive reconstruction of a region of interest (ROI) via the application of source analysis methods to scalp-recorded neuronal activities [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%